2012
DOI: 10.1103/physrevb.86.174519
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate magnetic fluctuations and Fermi surface topology in LiFeAs

Abstract: Using the angle-resolved photoemission spectroscopy (ARPES) data accumulated over the whole Brillouin zone (BZ) in LiFeAs we analyze the itinerant component of the dynamic spin susceptibility in this system in the normal and superconducting state. We identify the origin of the incommensurate magnetic inelastic neutron scattering (INS) intensity as scattering between the electron pockets, centered around the (π, π) point of the BZ and the large two-dimensional hole pocket, centered around the Γ-point of the BZ.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 39 publications
9
47
0
Order By: Relevance
“…If (π, π) spin fluctuations were strong enough, state B would be the most natural candidate. However, there is still no complete experimental evidence that spin fluctuations with large momentum transfer are strong 24 . There is indirect evidence that spin-fluctuations with a small momentum transfer may also be present -ferromagnetic fluctuations in the nonsuperconducting Li 1−y Fe 1+y As with y ≤ 0.04 are quite strong 46 .…”
Section: Iviii the Selection Of The S-wave Statethe Comparison Withmentioning
confidence: 99%
“…If (π, π) spin fluctuations were strong enough, state B would be the most natural candidate. However, there is still no complete experimental evidence that spin fluctuations with large momentum transfer are strong 24 . There is indirect evidence that spin-fluctuations with a small momentum transfer may also be present -ferromagnetic fluctuations in the nonsuperconducting Li 1−y Fe 1+y As with y ≤ 0.04 are quite strong 46 .…”
Section: Iviii the Selection Of The S-wave Statethe Comparison Withmentioning
confidence: 99%
“…In Ref. 21 the authors have identified the INS signal to be connected to scattering between the outer hole pocket and the electron pockets by using a simple tight-binding fit to the ARPES data, while involvement of the inner hole pocket was concluded in Ref. 20.…”
Section: B Evidence For Additional Contributions To Magnetic Scatteringmentioning
confidence: 99%
“…They could even have an effect on transport properties and electronic instabilities when the band edges (almost) coincide with the Fermi energy. This is the case in several classes of materials, such as in iron pnictide superconductors [25,26], transition metal silicides [27], or transition metal dichalcogenites [28]. …”
Section: Prl 111 216806 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%